A cost and return analysis of the fishing business of selected fish dealers in Shed, Sagkahan, Tacloban City. - Buenafrancisca, Eralyn C., et al.; de Asas, Jenny Beth S. (Tacloban City Eralyn C. Buenafrancisca, 2010)
This study traces the flow of fish products from the suppliers, to the fish dealers, and to the retailers. This study also evaluates the profitability of the fishing business of selected fish dealers (commission-based and engaged in both commission and direct fishing) in Shed, Sagkahan, Tacloban City. The cost-and-return analysis is used to determine the profitability of fishing business of each fish dealer by getting the annual revenue covering the months of December to January (lean season) and April to May (peak season). Findings show that by getting the average returns between those fish dealers who are into commission basis and in both commission and direct fishing, the latter gain more by Php3,704,320.344. Thus, engaging in both commission and direct fishing is more profitable than operating only through commission basis. Generally, the problem of most fish dealers relates to the supply of fish products.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science